Bacterial Microbiome in Wild-Caught Anopheles Mosquitoes in Western Thailand - Tainchum, Krajana; Dupont, Chloé; Chareonviriyaphap, Theeraphap; Jumas-Bilak, Estelle; Bangs, Michael J.; Manguin, Sylvie (Frontiers in Microbiology, 2020)
Among the complex microbial community living in the mosquito midgut, some bacteria (e.g., Enterobacter spp.) can deliver effector molecules with anti-Plasmodium effects suppressing the development of malaria parasites (Plasmodium falciparum) before the öokinete can penetrate the mosquito midgut epithelium. Despite knowledge of this phenomenon, only a few studies have defined the diversity of microbiota in wild-caught adult Anopheles species. The objective of this study was to analyze and compare the bacterial microbiota in different Anopheles species, including representatives of the primary malaria vectors in western Thailand. Wild female Anopheles species were sampled from malaria-endemic areas in Tak and Mae Hong Son provinces near the Thai-Myanmar border. Midgut/abdominal bacterial diversity was assessed by examining the 16S rRNA gene, V3 hypervariable region, using PCR-Temporal Temperature Gel Electrophoresis (PCR-TTGE) profiling and sequence analysis. A total of 24 bacterial genera were identified from eight Anopheles species. Five bacterial genera were newly reported in Anopheles mosquitoes (Ferrimonas, Megasphaera, Pectobacterium, Shimwellia, and Trabulsiella). Five genera, including Megasphaera, were detected exclusively in a single-malaria (Plasmodium vivax) infected Anopheles minimus and not observed in other non-infected mosquitoes. The use of PCR-TTGE provides the first characterization of the midgut bacterial microbiome present in wild adult Anopheles in Thailand. Evidence that microbiota might impact pathogen development (suppression) in Anopheles and thereby reduce the risk of pathogen transmission deserves more studies to describe the presence and better understand the biological role of bacteria in natural mosquito populations.